(untitled) (Medico Legal Update, 2020)
Matter: This is the first study in Al-Anbar governorate with this design aim to the detection of rotavirus group A (ROVA). Method: A total of (150) stool samples obtained from children <5 years with acute gastroenteritis were randomly collected from Maternity and Children at al-Anbar governorate from (1- 9-2019 to 1-2-2020); Rotavirus was detected by rapid test for stool samples and real-time polymerase chain reaction for blood and serum. Results: Out of total 150 stool sample there were 101(67.3%), 49(32.6%) Negative and positive result respectively, from rapid test. The result of RT-PCR from serum & blood were Thirty-one (31)81.57% of (38) samples positive for rotavirus & eight samples were no ct there was Significant value (0.0016)(0.0075) between PCR (blood, serum) test and Rapid test under p<0.05. Based on that RT-PCR was more sensitive & specific than rapid test